Correlation between pixel value of CBCT and Hounsfield Unit of MDCT on teeth and mandible cortical bone - A. Azhari; Rellyca Sola Gracea; I Made Agus Astika; Ali Thomas (Faculty of Dentistry, Universitas Gadjah Mada, 2018)
Cone-beam computed tomography (CBCT) is an imaging modality widely used in dentistry over multi detector computed tomography (MDCT). It is in view of its high resolution with relatively lower dose. MDCT is able to show Hounsfield Unit (HU) which is proportional to x-ray attenuation degree by the tissue. The x-ray attenuation degree in CBCT is shown in grayscale value with pixel values unit. The aim of this study was to determine the correlation of pixel values in CBCT with HU in MDCT. We used secondary data from RSGM Universitas Padjajaran patient who had CBCT and MDCT. Measurement was done on the cortical areas (lingual, buccal, and posterior side) of the mandible and teeth 47 (email, dentin, and pulp) with 5 regions of interest (ROIs) on each area. DICOM software was used for the measurement on CBCT and MDCT data. The result indicated a strong correlation between pixel value in CBCT and HU in MDCT on the cortical bone and teeth area (R=0.846). Linear regression resulted in an equation to derive HU value from pixel value of cortical bone and teeth area, which is y = 1,9011x + 177,15. The conclusion is HU can be derived from CBCT by converting with regression equation.